2018
DOI: 10.3889/oamjms.2018.314
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Lifestyle, Health Promotion Lifestyle Profile II And High Blood Pressure In University Students

Abstract: BACKGROUND:Identifying and controlling systemic arterial blood pressure is important in young people, and it is possible to reduce the frequency of systemic arterial hypertension by improving the lifestyle.AIM:The aim of the study is to assess the relationship between healthy lifestyle behaviors and systemic blood pressure in university students.MATERIALS:The study sample consisted of 200 university students from a state university in Edirne. Lifestyles and habits were evaluated with Health Promotion Lifestyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
5
4
0
Order By: Relevance
“…The present study found that the total prevalence of prehypertension independently of sex is 33.2%, while the hypertension prevail among 5.6% of respondents, respectively. Results of our study were similar to results of recent study in Turkey (Aynaci, Akdemir, 2018), where rate of hypertension was the same -5.6%. but the rate of prehypertension is very lower (8.6%), than our data.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study found that the total prevalence of prehypertension independently of sex is 33.2%, while the hypertension prevail among 5.6% of respondents, respectively. Results of our study were similar to results of recent study in Turkey (Aynaci, Akdemir, 2018), where rate of hypertension was the same -5.6%. but the rate of prehypertension is very lower (8.6%), than our data.…”
Section: Discussionsupporting
confidence: 92%
“…This was consistent with other studies (Gharaibeh et al 2012;Cheah et al, 2018Sakurai et al, 2006. This differences, according to may be due to data collection methods, the socioeconomic status of the evaluated population, and differences in healthy lifestyle behaviours (Aynaci, Akdemir, 2018). Also, the higher prevalence of elevated blood pressure among men could be explained by the fact that hormones, suchas testosterone, can play an important role in gender-associated differences in blood pressure regulation, as well as have a protective effect, such as oestrogen in females.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, the mean overall HPLP-II score of nonsmoking students was significantly higher than that of smoking ones, consistent with the results of Alzahrani et al in Saudi Arabia, Lolokote et al in China, and Aynaci and Akdemir in Turkey [ 12 , 26 , 30 ]. Smoking is an unhealthy behavior with negative impacts on lifestyle.…”
Section: Discussionsupporting
confidence: 91%
“…In a study conducted by Sen et al with 251 university students, the mean score of HLBS-II was found 118.0 ± 21.0 31 . According to previous studies, there were many studies conducted in this area and similar results were obtained [32][33][34][35] . Considering that the maximum obtainable score from healthy lifestyle behaviours is 208, the scores obtained from our study are moderate.…”
Section: Discussionsupporting
confidence: 73%